2016
DOI: 10.1128/jvi.01714-16
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Vesicular Stomatitis Virus Pseudotypes Bearing Essential Entry Glycoproteins gB, gD, gH, and gL of Herpes Simplex Virus 1

Abstract: Herpes simplex viruses (HSVs) are unusual in that unlike most enveloped viruses, they require at least four entry glycoproteins, gB, gD, gH, and gL, for entry into target cells in addition to a cellular receptor for gD. The dissection of the herpes simplex virus 1 (HSV-1) entry mechanism is complicated by the presence of more than a dozen proteins on the viral envelope. To investigate HSV-1 entry requirements in a simplified system, we generated vesicular stomatitis virus (VSV) virions pseudotyped with HSV-1 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 59 publications
4
28
0
Order By: Relevance
“…As expected, HSV-1 entered all receptor-bearing cells but not receptor-negative B78H1 or CHO-K1 cells (Fig 2A). VSVΔG-BHLD pseudotype also readily infected C10 cells but not parent B78H1 cells (Fig 2B), consistent with previous observations (27). VSVΔG-BHLD pseudotype also infected CHO-HVEM and CHO-nectin-1 cells in a receptor-dependent manner albeit with much lower efficiency (Fig 2B).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…As expected, HSV-1 entered all receptor-bearing cells but not receptor-negative B78H1 or CHO-K1 cells (Fig 2A). VSVΔG-BHLD pseudotype also readily infected C10 cells but not parent B78H1 cells (Fig 2B), consistent with previous observations (27). VSVΔG-BHLD pseudotype also infected CHO-HVEM and CHO-nectin-1 cells in a receptor-dependent manner albeit with much lower efficiency (Fig 2B).…”
Section: Resultssupporting
confidence: 92%
“…Previously, we showed that the VSVΔG-BHLD pseudotype efficiently entered C10 cells and that its entry recapitulated several important features of HSV-1 entry into susceptible cells: the requirement for gB, gH, gL, gD, and a gD receptor, and sensitivity to anti-gB and anti-gH/gL neutralizing antibodies (27). Here, we expanded this study to six additional HSV-1-susceptible cell lines and found that out of seven, only C10 and CHO-HVEM cells supported appreciable VSVΔG-BHLD entry.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…We believe that these peptides may be interacting with glycoprotein D, which is the least conserved protein between both viruses (85%) and is responsible for the activation of the heterodimer gH-gL [42,51]. …”
Section: Discussionmentioning
confidence: 99%
“…For herpes simplex viruses, the viral entry process takes place with the aid of 4 viral glycoproteins: gD, gB, gH, and gL, all of which have been proven to be essential for these viruses to carry out membrane fusion [42]. …”
Section: Discussionmentioning
confidence: 99%